Перша знахідка рідкісного гриба Hemileccinum depilatum (Redeuilh) Šutara на території природного заповідника «Медобори» - Романченко, Олександр Володимирович; Romanchenko O. (Львів: Галич-Прес, 2023)
Information about a new find of the rare mushroom species Hemileccinum depilatum, which is recently included in the Red Book of Ukraine is given. Brief information about the ecological features of the mushroom, its findings in other regions of Ukraine, and the nature protection status in Europe are summarized.
The first record of the rare fungus Hemileccinum depilatum (Redeuilh) Šutara from the territory of the Medobory Natural Reserve
Keywords: гриби; біорізноманіття; Червона книга; Україна; Поділля; Тернопільська область